PEMANFAATAN MEDIA SOSIAL AKUN INSTAGRAM @lkp.cakra.surakarta SEBAGAI SARANA INFORMASI BAGI CALON PESERTA PELATIHAN DI LEMBAGA KURSUS DAN PELATIHAN CAKRA SURAKARTA - Juvenia T, Chelsea Verro; Kusumo Aji, Haryo; Mahar Rizqi, Fikriana (Solidaritas, 2024)
Social media Instagram has become a popular medium as a means of information for the general public, one of which is the Instagram account @lkp.cakra.surakarta. The Instagram account @lkp.cakra.surakarta provides information regarding pre-employment wave schedules, training programs, recommendations and tips. This research aims to understand and describe the use of social media Instagram accounts as a means of information for prospective training participants at the Cakra Surakarta Course and Training Institute. This research uses a qualitative approach with descriptive methods. Data collection techniques are carried out using interviews, observation and documentation. Research subjects with 3 informants, namely the foundation owner, Instagram admin and prospective training participants. The validity of the data used is source triangulation. The research results show (1) Information Needs Approach: Utilization of Instagram social media to convey the latest/newest information. (2) Routine Information Approach: Regular posting schedules and relevant content help increase general public awareness about the programs offered (3) In-depth Information Approach: Presentation of call center tools to make it easier for prospective training participants to seek further information from the Instagram admin and present explanation of using the Instagram reels feature. (4) Information at a Glance Approach: Use of short posts such as Instagram stories and responsiveness to interactions via the comments column. Keywords: LKP, Instagram, Information Facilities.